2010
DOI: 10.1038/mp.2010.43
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of bipolar I disorder in the Han Chinese population

Abstract: We report the first genome-wide association study in 1000 bipolar I patients and 1000 controls, with a replication of the top hits in another 409 cases and 1000 controls in the Han Chinese population. Four regions with most strongly associated single-nucleotide polymorphisms (SNPs) were detected, of which three were not found in previous GWA studies in the Caucasian populations. Among them, SNPs close to specificity protein 8 (SP8) and ST8 a-Nacetyl-neuraminide a-2,8-sialyltransferase (ST8SIA2) are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 31 publications
7
123
1
1
Order By: Relevance
“…For example, a number of loss-of-function mutations of ankyrin-R are known to cause hereditary spherocytosis (9). Genetic variants of ankyrin-G are associated with bipolar disorder (10)(11)(12)(13)(14). Many missense mutations of ankyrin-B have been linked to inherited cardiac arrhythmia known as the "ankyrin-B syndrome" (15).…”
mentioning
confidence: 99%
“…For example, a number of loss-of-function mutations of ankyrin-R are known to cause hereditary spherocytosis (9). Genetic variants of ankyrin-G are associated with bipolar disorder (10)(11)(12)(13)(14). Many missense mutations of ankyrin-B have been linked to inherited cardiac arrhythmia known as the "ankyrin-B syndrome" (15).…”
mentioning
confidence: 99%
“…ANK3 was confirmed as associated with BD by a study involving individuals from Caucasian and African ancestry. Notably, this study found association with different SNPs in individuals of European and African ancestry [64], and studies in Japanese and Han Chinese populations showed no genome-wide significant findings [65,66].…”
Section: Genome-wide Association Studies In Bipolar Disordermentioning
confidence: 52%
“…This region had been reported in two previous genome-wide linkage scans of Eastern Quebec and Northeast Italian families as a common susceptibility region for both schizophrenia and bipolar disorder (Maziade et al, 2005;Vazza et al, 2007). Furthermore, previous studies reported that SNPs of the ST8 alpha-N-acetyl-neuraminide alpha-2,8-sialyltransferase 2 gene (ST8SIA2), located around 2.5 Mb proximal to the linkage peak (rs2028299) on chromosome 15q26.1, were associated with schizophrenia or bipolar I disorder in Asian population (Arai et al, 2006;Tao et al, 2007;Lee et al, 2011). However, this region did not show evidence of linkage for schizophrenia in our previous genome-wide linkage scan (Hong et al, 2009).…”
Section: Discussionmentioning
confidence: 95%